Mengungkap Nilai Filosofi Stoicism dalam Film The Shawshank Redemption (Kajian Semiotika Charles Sanders Peirce) - Muhajir, Muhammad Ali (Jurnal Nomosleca, 2024)
This research aims to reveal the values of Stoicism represented in the film "The Shawshank Redemption". The focus of this research is the representation of the philosophical values of Stoicism with objects in the form of scenes, dialogue and stills in the film. The method used in this research is semiotic analysis with a qualitative approach. This research analyzes data documentation in the form of symbols, images, text, and so on through Charles Sanders Peirce's semiotics which divides signs based on symbols, objects, and interpretants known as triadic triangles. Based on the results of the analysis, many of Stoicism's wisdom values include wisdom, justice, self-control and courage, reflected through the journey of the main character, Andy Dufresne.